Unpacking green growth in SMEs: A framework for dynamic capabilities, value co-creation, and sustainable performance - Aghnia Nadhira Aliya Putri; Pri Hermawan; Isti Raafaldini Mirzanti; Maureen Meadows; Rosie Sadraei (Sustainable Futures)
This study examines how green dynamic capabilities and value co-creation drive sustainability transitions in small and medium-sized enterprises (SMEs), enabling them to integrate sustainability into their business models and improve environmental, economic, and social performance. A systematic literature review using PRISMA guidelines analyzed 108 peer-reviewed articles from the Scopus database. Thematic analysis identified key factors influencing SME sustainability through dynamic capabilities and value co-creation. The findings reveal that green dynamic capabilities—sensing, seizing, and transforming sustainability opportunities—are essential for SMEs to adapt to regulatory, market, and technological shifts. Value co-creation, facilitated by stakeholder collaboration, digital technology adoption, and regulatory engagement, further enhances sustainability outcomes. Mediating factors, including financial accessibility, digital transformation, institutional support, and market pressure, influence how effectively SMEs integrate green practices. The study developed a framework showing that SMEs should enhance green capabilities and stakeholder engagement to overcome resource constraints, while policymakers and industry players must strengthen institutional support, regulatory incentives, and tailored green financing. This study integrates green dynamic capabilities and value co-creation into the structured framework.